Exploring Vocabulary Teaching Strategies in Secondary High School: A Qualitative Method at SMP Negeri 1 Galesong Utara Kabupaten Takalar - Nurmuslimah Qadri; Muhammad Hasbi; Nur Aeni (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study explores the strategies used by English teachers in teaching vocabulary at SMP Negeri 1 Galesong Utara, Kabupaten Takalar. Using a mixed-method approach, this study combines qualitative and quantitative data to analyze the implementation of vocabulary teaching strategies effectiveness. Qualitative data were obtained through classroom observation, teacher and student interviews, and document analysis, while quantitative data were collected from pre-tests and post-tests conducted in class VII.1. The result of the study indicated that teachers used various methods, including Total Physical Response (TPR) and vocabulary memory games, supported by contextual learning tools such as multimedia and group collaboration. The strategies were adapted based on students' diagnostic results to accommodate diverse learning needs. Statistical analysis showed a significant increase in students' vocabulary mastery after the implementation of these strategies, indicating their effectiveness. This study contributes to the understanding of dynamic and differentiated vocabulary teaching strategies in junior high schools and offers practical implications for improving English learning outcomes in similar educational contexts.